Leucovorin, fluorouracil, and oxaliplatin plus bevacizumab versus S-1 and oxaliplatin plus bevacizumab in patients with metastatic colorectal cancer (SOFT): an open-label, non-inferiority, randomised phase 3 trial - Yamada, Yasuhide; Takahari, Daisuke; Matsumoto, Hiroshi; Baba, Hideo; Nakamura, Masato; Yoshida, Kazuhiro; Yoshida, Motoki; Iwamoto, Shigeyoshi; Shimada, Ken; Komatsu, Yoshito; Sasaki, Yasutsuna; Satoh, Taroh; et al. (The lancet oncology, 2013)
Studies done in Asia have shown that a regimen of S-1 plus oxaliplatin (SOX) has promising efficacy and safety in patients with metastatic colorectal cancer. We aimed to establish whether SOX plus bevacizumab is non-inferior to mFOLFOX6 (modified regimen of leucovorin, fluorouracil, and oxaliplatin) plus bevacizumab as first-line chemotherapy for metastatic colorectal cancer. We undertook an open-label, non-inferiority, randomised phase 3 trial in 82 sites in Japan. We enrolled individuals aged 20–80 years who had metastatic colorectal cancer, had an Eastern Cooperative Oncology Group performance status of 0 or 1, had assessable lesions, had received no previous chemotherapy or radiotherapy, could take drugs orally, and had adequate organ function. Eligible patients were randomly assigned (1:1) to receive either mFOLFOX6 plus bevacizumab (on day 1 of each 2-week cycle, 5 mg/kg intravenous infusion of bevacizumab and a simultaneous intravenous infusion of 85 mg/m2 oxaliplatin, 200 mg/m2l-leucovorin, 400 mg/m2 bolus fluorouracil, and 2400 mg/m2 infusional fluorouracil) or SOX plus bevacizumab (on day 1 of each 3-week cycle, 7·5 mg/kg intravenous infusion of bevacizumab and 130 mg/m2 intravenous infusion of oxaliplatin; assigned dose of S-1 twice a day from after dinner on day 1 to after breakfast on day 15, followed by 7-day break). Randomisation was done centrally with the minimisation method, with stratification by institution and whether postoperative adjuvant chemotherapy had been given. Participants, investigators, and data analysts were not masked to treatment assignment. The primary endpoint was progression-free survival (PFS), which was defined as the interval between enrolment and progressive disease (≥20% increase in sum of longest dimensions of target lesions from baseline, or appearance of new lesions) or death, whichever came first. The primary analysis was done by modified intention to treat. This trial is registered with the Japan Pharmaceutical Information Center, number JapicCTI-090699. Between Feb 1, 2009, and March 31, 2011, 512 patients underwent randomisation. 256 patients assigned to receive SOX plus bevacizumab and 255 assigned to receive mFOLFOX6 plus bevacizumab were included in the primary analysis. Median PFS was 11·5 months (95% CI 10·7–13·2) in the group assigned to mFOLFOX6 plus bevacizumab and 11·7 months (10·7–12·9) in the group assigned to SOX plus bevacizumab (HR 1·04, 95% CI 0·86–1·27; less than non-inferiority margin of 1·33, pnon-inferiority=0·014). The most common haematological adverse events of grade 3 or higher were leucopenia (21 [8%] of 249 patients given mFOLFOX6 plus bevacizumab included in safety analysis vs six [2%] of 250 given SOX plus bevacizumab; p=0·0029) and neutropenia (84 [34%] vs 22 [9%]; p<0·0001). Grade 3 or higher anorexia (13 [5%] vs three [1%]; p=0·019) and diarrhoea (23 [9%] vs seven [3%]; p=0·0040) were significantly more common in patients given SOX plus bevacizumab than in those given mFOLFOX6 plus bevacizumab. We recorded seven treatment-related deaths (three in the group given mFOLFOX6 plus bevacizumab; four in that given SOX plus bevacizumab). SOX plus bevacizumab is non-inferior to mFOLFOX6 plus bevacizumab with respect to PFS as first-line treatment for metastatic colorectal cancer, and could become standard treatment in Asian populations. Taiho.